Daya Tampung Beban Pencemar Sungai Badung di Desa Dauh Puri Kota Denpasar dengan Model QUAL2KW - dody setiawan; I G B Sila Dharma; I Wayan Budiarsa Suyasa (Master Program of Environmental Science, Postgraduate Program of Udayana University, 2017)
Badung River is flow through two regencies of Badung and Denpasar that has 25.17 km length. People actually use Badung River for tourism, irrigation, drainage system and as the exile of wastewater from all activities along the river. The water quality of Badung River has exceeded the threshold limits.Therefore, It is needed to determinate the carrying capacity of Badung river. Because of the pollution, the water quality has degraded. The objective of this research is knowing the sources of pollution and load capacity of Badung river at Dauh Puri village using Qual2kw model, to define that amount of pollutant that are allowed to exile in Badung River. The water quality parameter that analyzed is BOD, COD, and TSS. This research divided into three segments, and four scenarios of simulations to know allowed loading rate of pollutant along the river. The callculates and allocate pollutant reduction levels necessary to meet approved water quality standards. The result of simulation using Qual2kw showing that BOD has over its limit, meanwhile for COD parameter, the loading rate is between 536,21 to 1360,32 kg/day and TSS loading rate between 2235,92 to 4252,90 kg/day. Keywords: Badung River, Qual2KW 5.1, Loads Capacity, Water Quality